Evaluation of Oral Health Education Programme among Parents of Intellectually Disabled Children In Bengaluru - T, Nagaland; Kadanakuppe, Sushi; R, Rekha; Chandran, Thara; H, Cyril Benedict; Sahana, U Baratakke (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Good oral hygiene maintenance is one of the most important factors in oral health care, which of course is exceptionally difficult for a mentally or physically handicapped. Since parents are responsible for almost all health issues related to their children, their role in modelling their children toward practicing preventive oral health throughout life is crucial. Objectives: The program aimed to educate the parents about the importance of oral health care and to motivate them with regard to prevention and improve the oral hygiene and oral health of their intellectually disabled children. Materials and methods: Data was collected from the parents and their disabled children. The questionnaire for parents contains demographic data and KAP towards oral health of intellectually disabled children and baseline and post interventional Gingival and Plaque scores were recorded for their children. Paired and unpaired t tests were used to assess the change in plaque and gingival scores and KAP scores with 5% as level of significance. Results: At baseline, no significant differences were found at Plaque and Gingival scores of the disabled children and Knowledge, Attitude and Practice of their parents between the interventional and control groups. At post intervention, Plaque and Gingival scores were significantly decreased (p<0.001) and significant improvement in the Knowledge, Attitude and Practice was observed (p<0.001) in interventional group when compared to controls. Conclusion: The intervention was thus deemed successful in improving parents Knowledge, Attitude and practicing behaviours and also improved the oral hygiene status of their disabled children.